Jobless Recovery and Structural Change: A VAR Approach. (June 2017) - Chen, Li-Hsueh; Cui, Zhen
This study uses a vector autoregression approach to examine the link between jobless recoveries and the fast employment expansion in finance, health and education (FHE) sectors. Both reduced-form estimates and impulse responses indicate a negative effect of the expansion on aggregate employment. While the expansion Granger causes aggregate employment fluctuations, up to 40 per cent of the error variance of those fluctuations can be explained by innovations in the expansion. Moreover, movements in aggregate employment are reduced by 25 per cent when the expansion is accounted for. Therefore, the fast expansion of the FHE sectors is shown to have notably contributed to the onset of jobless recoveries. JEL Classification: E24, E32, C32